Quantitative Analysis of Flavonoids in Glycyrrhiza uralensis Fisch by 1H-qNMR - Ping Yu; Qian Li; Yanmei Feng; Yuying Chen; Sinan Ma; Xiaoqin Ding (Journal of Analytical Methods in Chemistry)
Objective. To establish a method for simultaneous determination of liquiritin, liquiritigenin, and isoliquiritinin glycyrrhizin using hydrogen nuclear magnetic resonance quantitative technology (1H-qNMR). Methodology. Deuterated dimethyl sulfoxide was used as the solvent, and dichloromethane was used as the internal standard. The probe temperature was 298.0 K, the pulse sequence was Zg30, the number of scans was 16, and relaxation delay (D1) was 10 s. Quantitative characteristic signal peaks were δ 4.891∼4.878 ppm, δ 8.187∼8.172 ppm, and δ 6.790∼6.776 ppm for liquiritin, isoliquiritin, and liquiritigenin, respectively. Results. The experimental result showed that the content of flavonoids in Licorice, from Chifeng, Inner Mongolia, was the highest. Conclusion. In this study, a new method for determination of three flavonoids in Licorice using 1H-qNMR was established. This experimental method has the advantages of accuracy, efficiency, and economy. It lays a foundation for the study on the determination of flavonoids content in licorice by proton nuclear magnetic resonance spectroscopy.